Overview of meteorological and hydrological conditions in the Hornád river basin. Issue 1 (1st September 2022) - Nagy, P; Garaj, M; Hlinková, M
Abstract: The assessment of deficit and surplus volumes is important for assessing the effects of climate change on water management. Climate change needs to be taken into account in water management. At a time of climate change, there is a frequent occurrence of such periods, but also torrential rains, it is necessary to assess the quantity and quality of surface waters. Building structures must be designed in such a way that, during the period of torrential rains, they retain water from the surface runoff and prevent any damage that could arise from the original; sufficient water and dry season must be ensured during the period. Water shortages can also be caused by increased water consumption. The assessment of the volume of water in the Hornád river basin has shown that it is possible to mitigate climate change.